The Role of Emotional Intelligence in Organizational Success - Garg, Ambarish; Saxena, Swati (AG Volumes, 2024)
It is thought that emotional intelligence (EI) helps people function at greater levels. Achieving greater performance levels with less resources has become crucial in light of the present pandemic and global economic crisis. In this article review the various literature’s study on role of emotional intelligence in organizational success. This review concluded that the emotional intelligence (EI) plays a crucial role in organizational success, particularly in the public sector, where diverse policies and stakeholder interactions shape performance. This study highlights the positive impact of self-awareness on job performance, while inspiring performance also emerges as a key predictor. While self-management and awareness of others show mixed effects, EI remains strongly linked to employee behavior, career success, and overall organizational performance. Effective EI training enhances social networks and influences personal and professional interactions. Notably, the regulation of emotions is a major contributor to job performance, enabling employees to manage their moods and behaviors for optimal workplace success.